2019
DOI: 10.1111/japp.12371
|View full text |Cite
|
Sign up to set email alerts
|

Punishment for Mob‐based Harms: Expressing and Denouncing Mob Mentality

Abstract: Larry May's and Kenneth Shockley's discussions of punishment for mob-based harms fall back on the idea of individual mens rea. They recognise that the mens rea element is complicated by the fact that an individual's intentional actions in the context of mob activity have a collective dimension to them, either because they are 'group-based', or because they are enabled or constrained by the collective's 'normative authority'. However, their accounts of punishment fail to adequately reflect this complication. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Most participants were unaware that they were being controlled or manipulated by other racers in their group as verbal communication becomes difficult in a large group. Similar studies have shown that in a group of more than 200 people, only 5% of people in the group is needed to influence the direction and motivation of its members (Akoi, 2019;Bowden et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…Most participants were unaware that they were being controlled or manipulated by other racers in their group as verbal communication becomes difficult in a large group. Similar studies have shown that in a group of more than 200 people, only 5% of people in the group is needed to influence the direction and motivation of its members (Akoi, 2019;Bowden et al, 2021).…”
Section: Discussionmentioning
confidence: 80%